PENGARUH KOMUNIKASI DAN KOMPENSASI TERHADAP KINERJA PENGELOLA BANK WAKAF MIKRO MAWARIDUSSALAM - Radiansyah, M; Munawaroh, Munawaroh; Putri Silalahi, Cita Ayni (Yayasan Rahmat Islamiyah, 2024)
The aim of this research is to determine: The influence of communication on the performance of BWM Mawaridussalam managers, the influence of compensation on the performance of BWM Mawaridussalam managers, the influence of communication and compensation together on the performance of BWM Mawaridussalam managers. The research uses quantitative methods. The research stages are the preparation of research instruments where the research instrument that will be used is a questionnaire. The questionnaire will be filled out by the BWM Mawaridussalam manager. Then data collection will be collected by distributing questionnaires to BWM Mawaridussalam managers. And data analysis, where the data that has been collected will be analyzed using multiple regression analysis. The targeted research outcomes of this research are as follows: The results of this research are expected to provide a better understanding of the influence of communication and compensation on the performance of BWM Mawaridussalam managers. The results of this research are expected to be a consideration for BWM Mawaridussalam in improving the performance of its managers. It is hoped that this research can contribute to the development of BWM management theory and practice.